European vegetation survey: Update on progress - Mucina, Ladislav; Rodwell, J.; Pignatti, S. (1996)
Progress in the European Vegetation Survey is described. 25 countries are now represented in a network committed to common data standards in phytosociological survey, the development of compatible software for data analysis and mapping, the encouragement of national programmes and the development of an overview of European plant communities. Advances in each of these areas of activity is summarised and plans for the future are outlined, most notably the production of a book 'The Vegetation of Europe'.